Effects of the acute exposition to glyphosate-based herbicide on oxidative stress parameters and antioxidant responses in a hybrid Amazon fish surubim (Pseudoplatystoma sp) - Gindri Sinhorin, Valeria Dornelles; Sinhorin, Adilson Paulo; Santos Teixeira, Jhonnes Marcos dos; Lazarotto Mileski, Kelly Marcia; Hansen, Paula Carine; Andrade Moreira, Paula Sueli; Kawashita, Nair Honda; Baviera, Amanda Martins [UNESP]; Loro, Vania Lucia (Elsevier B.V., 2014)
The aim of this study was to investigate the effects of acute glyphosate (active ingredient) exposure on the oxidative stress biomarkers and antioxidant defenses of a hybrid surubim (Pseudoplatystoma sp). The fish were exposed to different herbicide concentrations for 96 h. The thiobarbituric acid-reactive substances (TBARS), protein carbonyls and antioxidant responses were verified. The 15 mg a.p L-1 of herbicide resulted in the death of 50% of the fish after 96 h. An increase in liver and muscle TBARS levels was observed when fish were exposed to the herbicide. The protein carbonyl content was also increased in the liver (4.5 mg a.p L-1 concentration) and brain (2.25 mg a.p L-1 concentration). The antioxidant activities decreased in the liver and brain after exposure to herbicide. Levels of ascorbic acid in the liver (2.25 mg a.p L-1 and 4.5 mg a.p L-1 concentrations) and brain (2.25 mg a.p L-1 concentration) were increased post-treatment. Levels of total thiols were increased in the liver and brain (2.25 mg L-1 and 7.5 mg a.p L-1, respectively). Glyphosate exposure, at the tested concentrations affects surubim health by promoting changes that can affect their survival in natural environment. Some parameters as TBARS and protein carbonyl could be early biomarkers for Roundup exposure in this fish species. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Fish farmers; Hybrid Amazon fish; Pesticide; Oxidative stress; Soybean monoculture; Roundup